Pengaruh Gaya Kepemimpinan Transformatif, Motivasi, dan Perlindungan Serta Pemenuhan Hak Terhadap Kinerja Karyawan Penyandang Disabilitas di PT. Citibank Indonesia - Suharyanto, Suharyanto; Aprillia, Cindi; Ameliaratri, Rizky; Andryani, Novi (Innovative: Journal Of Social Science Research, 2024)
This article reviews the Influence of Transformative Leadership Styles, Motivation, and Protection and Fulfillment of Rights on the Performance of Employees with Disabilities. In writing this article, people with disabilities also get and have the same rights protection as other employees. The Indonesian government issued Law Number 8 of 2016 which discusses Persons with Disabilities (UUPD). This research was conducted on 40 employees with disabilities at PT. Citibank Indonesia. This study uses a qualitative method by conducting direct interviews with employees with disabilities. In this case, employees with disabilities also have the performance needed by the company. The number of employees with disabilities in Indonesia is also very small, this is due to the gap between competencies and acceptance requirements in the work environment, and the low education and skills of people with disabilities.